The Effect of Motivation and Job Satisfaction on Employee Performance at the Halal Product Assurance Agency (BPJPH) Jakarta Based on Aswaja Nahdlatul Ulama Values - Cariza Ayu Ardaneswari; Iqbal Saujan (Lakpesdam PCNU Kota Salatiga, 2026)
This study is grounded in the importance of human resource development in improving employee performance within public service institutions, particularly the Halal Product Assurance Agency (BPJPH) Jakarta. Employee performance is not only influenced by managerial aspects such as motivation and job satisfaction but also by ethical values that shape organizational work culture. Therefore, this study aims to examine the partial effect of motivation on employee performance, the partial effect of job satisfaction on employee performance, the simultaneous effect of motivation and job satisfaction on employee performance, and to assess the extent to which work patterns at BPJPH align with the values of Ahlussunnah wal Jama’ah (Aswaja) of Nahdlatul Ulama. This research employs a quantitative approach with a field research design. The population consists of 205 BPJPH employees, with a sample of 70 respondents selected using a convenience sampling technique. Data were collected through questionnaires, observations, and interviews, and analyzed using descriptive statistics and multiple linear regression with the assistance of IBM SPSS Statistics. The findings reveal that motivation has a positive but not significant partial effect on employee performance, while job satisfaction has no positive and significant partial effect. However, motivation and job satisfaction simultaneously have a significant effect on employee performance. Furthermore, the work patterns at BPJPH generally reflect Aswaja values tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i’tidal (justice) although improvements are still needed in incentives, career development, and recognition systems. This study contributes to the development of value-based human resource management, particularly in integrating Islamic values into professional work ethics within public service institutions.